ON MATRIX SUMMABILITY OF JACOBI SERIES - LAL, SHYAM (Tamkang Journal of Mathematics, 1999)
In this paper a new theorem on Matrix Summability of Jacobi series is established This theorem is a generalization of several known and unknown results.